Association between long sleep duration and increased risk of obesity and type 2 diabetes: A review of possible mechanisms. (August 2018) - Tan, Xiao; Chapman, Colin D.; Cedernaes, Jonathan; Benedict, Christian
Summary: For the last two decades research has revealed an alarming association between short sleep duration and metabolic disorders. In tandem, the hormonal, behavioral, and genetic mechanisms underlying this relationship have been extensively investigated and reviewed. However, emerging evidence is revealing that excessive sleep duration has remarkably similar deleterious effects. Unfortunately, to date there has been little attention to what drives this connection. This narrative review therefore aims to summarize existing epidemiological findings, experimental work, and most importantly putative molecular and behavioral mechanisms connecting excessive sleep duration with both obesity and type 2 diabetes mellitus. It will also address recent findings suggesting a worrisome bidirectional effect such that metabolic disorders create a positive feedback loop which further perpetuates excessive sleep.